Computerised calibration system for radiosonde pressure sensors - SRIVASTAV, S. K.; GUPTA , M. K.; BHARADWAJ, K. L. (MAUSAM, 1993)
A computer bast1d data acquisition system has been designed for the calibration of pressure sensors used in MK III Indian radiosondes. The system can calibrate 64 baroswitchesin one cycle and gives a tabular printout of pressure values at various contact numbers. This replaces the analog type of recording system, which was in use for the last few decades. The present system gives better accuracy and resolution and avoids human judgement and errors.